PENGGUNAAN DEIKSIS DALAM NOVEL MY IDIOT BROTHER KARYA AGNES DAVONAR - Ambay, Yulita; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe research about person deixis, place, time and social in Agnes Davonar's My Idiot Brother novel focused on the description of the form and the meaning of person deixis, place, time and social and relationship between the persona deixis and social. The form of this research was qualitative with descriptive method. The data in this research was the person deixis, place, time and social contained in the novel My Idiot Brother. The sources of this research was the novel My Idiot Brother by Agnes Davonar. The data collection technique in this research was using documentary. The technique testing the validity of data in this research was diligence of observation and reference coverage. Based on data analysis on Agnes Davonar's My Idiot Brother novel found 16 forms of person deixis, 6 forms of place deixis, 5 forms of time deixis, and 9 forms of social deixis. The form of the persona deixis is found to be the first person singular, first person plural, second person singular, second person plural, third person singular and third person plural.                                     Keywords: Form, Meaning, Deixis, Novel